2014
DOI: 10.1089/end.2014.0135
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemia and Low High-Density Lipoprotein Cholesterolemia Are Associated with Increased Hazard for Urolithiasis

Abstract: Our study implies that dyslipidemia may play a crucial part in urinary stone risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 26 publications
5
27
1
Order By: Relevance
“…We were reassured by the results obtained by Kang et al [18] from South Korea. They showed that increased HDL was protective.…”
Section: Discussionsupporting
confidence: 62%
“…We were reassured by the results obtained by Kang et al [18] from South Korea. They showed that increased HDL was protective.…”
Section: Discussionsupporting
confidence: 62%
“…The 11 selected studies contained 282 479 participants (ranging from 694 to 116 536) . They were published between 2008 and 2017.…”
Section: Resultsmentioning
confidence: 99%
“…The regional distribution of the studies included were as follows: nine from Asia, one from Europe and one from the USA. Eight studies reported the association between TG and urolithiasis, whereas nine studies reported the relationship between HDL and urolithiasis . Three studies showed the association of any dyslipidemia traits (not separately reported TG, HDL, TC, LDL) with urolithiasis .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kang et al. found that people with a tendency to develop kidney stones were more likely to have high triglycerides and low HDL cholesterol. Torricelli et al.…”
Section: Discussionmentioning
confidence: 99%